Driving through demands: How self-efficacy shapes the impact of job stress on private bus drivers in India - Ranjan, Rajesh; Singh, Rashmi; Tripathi, Saumya (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the relationship between various job demands namely, quantitative demands, work pace, emotional demands, and the demand to suppress emotions and their psychological and job-related effects, including stress, depressive symptoms, and job satisfaction, among private bus drivers in North India. A sample of 300 drivers was surveyed using a Hindi-translated version of the Copenhagen Psychosocial Questionnaire. Data analysis was conducted using SPSS to test the proposed research hypotheses. The findings highlight the significant moderating role of self-efficacy in this context. Specifically, self-efficacy was found to positively influence job satisfaction while mitigating levels of stress and depressive symptoms. Furthermore, job demands exhibited a substantial impact on the respondents, which was notably moderated by their self-efficacy levels. The study offers both practical and theoretical contributions by providing insights that can help bus operators develop targeted interventions to enhance driver well-being and job performance. Limitations of the study and directions for future research are also discussed.